2019
DOI: 10.1158/1535-7163.mct-19-0424
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide Augments the Antitumor Activities of Eps8 Peptide-Specific Cytotoxic T Lymphocytes against Multiple Myeloma

Abstract: Cancer immunotherapy is a promising new approach to cancer treatment. It has been demonstrated that a high number of tumor-specific cytotoxic T cells (CTL) is associated with increased survival in patients with multiple myeloma. Here, we focused on EGFR pathway substrate 8 (Eps8) as a candidate tumor-associated antigen (TAA) in multiple myeloma. Previous work has shown that Eps8-based immunotherapy in HLA-A2 þ cancer patients may result in efficient antitumor immune responses against diverse tumor types. To im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…[12][13][14] Peptide-based treatments, either as monotherapy or in combination with other treatment modalities, have exhibited robust induction of peptide-specific immune responses and clinical benefits in MM. [15][16][17][18][19] Phase I and II clinical studies have demonstrated that peptide vaccines based on MM-associated antigens are well-tolerated and capable of eliciting antigen-specific T cell responses, either for preventing the progression of smoldering multiple myeloma (SMM) to active MM or reducing the relapse rate following ASCT. [15,16] In murine MM models, treatment with an HLA-A*02:01-restricted peptide vaccine derived from multiple myeloma special antigen-1 and Dickkopf-1 resulted in tumor volume reduction, attenuation of bone destruction, and significant improvement in survival.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Peptide-based treatments, either as monotherapy or in combination with other treatment modalities, have exhibited robust induction of peptide-specific immune responses and clinical benefits in MM. [15][16][17][18][19] Phase I and II clinical studies have demonstrated that peptide vaccines based on MM-associated antigens are well-tolerated and capable of eliciting antigen-specific T cell responses, either for preventing the progression of smoldering multiple myeloma (SMM) to active MM or reducing the relapse rate following ASCT. [15,16] In murine MM models, treatment with an HLA-A*02:01-restricted peptide vaccine derived from multiple myeloma special antigen-1 and Dickkopf-1 resulted in tumor volume reduction, attenuation of bone destruction, and significant improvement in survival.…”
Section: Introductionmentioning
confidence: 99%
“…81 These ACTs are primarily used for the treatment of hematological malignancies. 46,47,82,83 Limited lymphocyte infiltration and immunosuppressive microenvironment, which are associated with abnormal tumor vasculature, are major challenges to the effectiveness of ACT in solid tumors.…”
Section: Immunotherapymentioning
confidence: 99%
“…Limited or absence of T-cell infiltration within tumors is a significant factor that compromises the effectiveness of various immunotherapies, such as ICIs and ACT therapy. 82,89 The tumor vasculature plays a crucial role as the entry point for circulating leukocytes, 44 and therefore, abnormal vessels within tumor tissues may contribute to the immune escape of tumor cells. 84,90 Mechanistically, the abnormal vascular structure contributes to compromised lymphocyte infiltration.…”
Section: Mechanism Of Synergistic Effect Between Anti-angiogenic Agen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although lenalidomide has been shown to improve progression-free survival (PFS) and overall survival (OS) in multiple myeloma (MM) (9), the effects of lenalidomide alone have not been shown in GBM. Lenalidomide had little effect on the induction of apoptosis in GBM cells; however, it regulated the functions of CAR T cells and improved patient outcomes in combination with peptide vaccines in previous studies (10)(11)(12). The combination of the peptide vaccine and an antiprogrammed cell death protein 1 (PD1) antibody therapy worked synergistically against GBM in a previous study (13).…”
Section: Introductionmentioning
confidence: 99%